IMPLEMENTASI PERENCANAAN STRATEGIS DALAM MENINGKATKAN MUTU TENAGA PENDIDIK DI SMKN 1 NEGERIKATON KABUPATEN PESAWARAN - Sri Hartati; Sultan Syahril; Rina Setyaningsih (UNISAN JURNAL, 2022)
The purpose of this study is to determine the implementation of strategic planning in improving the quality of educators. To answer the research problem, this type of field research is used. Data collection techniques in this study include: observation, interviews, and documentation. The data analyzed are data reduction, data presentation, and data verification or drawing conclusions. Then tested the validity of the data with source triangulation techniques and research techniques. The conclusion from the results of this study is that the implementation of strategic planning at SMKN 1 Negerikaton is good, including the implementation of strategic planning. In the strategic planning step, the principal takes several steps, namely strategic planning, strategic planning implementation, and strategic planning evaluation. The principal took several planning steps, namely forming a special team as the initiator of the strategic planning from various qualified resources, dividing groups with their respective tasks; identify and review various laws and regulations and school policies regarding improving the quality of educators; creating the vision, mission, and values ​​of the madrasa; analyze SWOT by identifying the strengths, weaknesses, strengths, and threats, which are contained in SMKN 1 Negerikaton according to the actual conditions in the school. At this step strategic issues have not been analyzed according to the level of urgency; formulating strategies to manage issues by formulating planned programs and activities to address strategic issues; as well as reviewing and adopting the strategies set out in the strategic plan.